2018
DOI: 10.3389/fimmu.2018.00806
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons, Autophagy and Host Metabolism in Leprosy

Abstract: For those with leprosy, the extent of host infection by Mycobacterium leprae and the progression of the disease depend on the ability of mycobacteria to shape a safe environment for its replication during early interaction with host cells. Thus, variations in key genes such as those in pattern recognition receptors (NOD2 and TLR1), autophagic flux (PARK2, LRRK2, and RIPK2), effector immune cytokines (TNF and IL12), and environmental factors, such as nutrition, have been described as critical determinants for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 95 publications
2
34
0
Order By: Relevance
“…Autophagy is a cellular process facilitating the elimination of intracellular pathogens including Mtb ( 39 ). Antimicrobial autophagy was shown to be inhibited by Mycobacterium leprae through upregulation of IFN-β and autocrine IFNAR activation which in turn increased expression of the autophagy blocker OASL (2′-5′-oligoadenylate synthetase like) ( 40 ). Whether there is a link between the 7 α ,25-OHC-induced reduction of IFN-β production and the increase in autophagy remains to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a cellular process facilitating the elimination of intracellular pathogens including Mtb ( 39 ). Antimicrobial autophagy was shown to be inhibited by Mycobacterium leprae through upregulation of IFN-β and autocrine IFNAR activation which in turn increased expression of the autophagy blocker OASL (2′-5′-oligoadenylate synthetase like) ( 40 ). Whether there is a link between the 7 α ,25-OHC-induced reduction of IFN-β production and the increase in autophagy remains to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another important PRR involved in innate immune activation is the cytosolic sensor NOD-2. The receptor recognizes M. leprae muramyl dipeptide (MDP) and preferentially induces dendritic cell differentiation through the secretion of the pro-inflammatory cytokine IL-32 [103]. In addition, NOD-2 activation initiates a leucine-rich repeat kinase 2 (LRRK2)-dependent pro-inflammatory response as well as autophagy.…”
Section: Modulation Of Innate Immunitymentioning
confidence: 99%
“…Several studies have shown that M. leprae infection promotes modifications of host cell metabolism and results in conversion of the host immune response. One of the most important metabolic pathways in correlation with the spectrum of clinical forms is, among others, the regulation of lipid metabolism [101,103]. Enhancement of lipid metabolism is mainly observed in lepromatous lesions with the appearance of foamy macrophages (Virchow cells) composed of host-oxidized phospholipids.…”
Section: Metabolic Immunitymentioning
confidence: 99%
See 2 more Smart Citations